Orff Music Therapy: History, Principles and Further Development - Melanie Voigt (Approaches: Music Therapy & Special Music Education, 2013)
Orff Music Therapy, a developmental approach to music therapy, was developed by Gertrud Orff within the framework of social paediatrics in Munich, Germany. A short historical background of Orff Music Therapy is discussed. The history of the clinical setting in which it was developed is described as is Gertrud Orff’s professional background. The role of Orff-Schulwerk in Orff Music Therapy and the development of theoretical foundations are discussed. Current principles and practice of Orff Music Therapy, illustrated by a case example show how the profile of Orff Music Therapy has developed. On the basis of the case example, theory is related to practice. Finally, changes influencing Orff Music Therapy today, training and research are considered.